Evaluation of High Yielding Ragi Varieties for Western Zone of Tamil Nadu - kumar, S. Saravana (Indian Journal of Hill Farming, 2019)
Ragi (Eleusine coracana) is the major staple food crop cultivated in the western zone of Tamil Nadu. However the productivity is quite low. An attempt was made to identify suitable high yielding varieties for this region through on farm trials in rode District during 2013-14. The study revealed that ML-365 recorded higher grain yield of 2584.5 kg/ha and high number of tillers 8.28 which was on par with Co-15Â  ariety compared to other varieties. Higher net return of Rs. 31605.5 /ha and benefit cost ratio of 2.81 was recorded in ML-365 compared to the other varieties. Farmers satisfied with ML-365 due to its high tillering& yielding nature. Considering the above facts, ML-365 would be a better option to the farming community forÂ  enhancing the productivity of ragi in western zone of TamilNadu.